Media dan Demokrasi di Era Global: Studi Dakwah Islam Kontemporer di Indonesia - Rachmawati, Farida (UIN Walisongo Semarang, 2017)
Globalization has affected all the cultural subsystems of today's society, especially in media. How Islamic da’wa opportunities in the midst of media globalization is the focus of this article. Library studies have been used in this study. The result shows that Islamic da’wa is in the marginal position and has not been able to become a major player. There are four opportunities that can be used in preaching Islam in the era of media globalization. First, the freedom of information media is filled with enhancing creativity in making Islamic content more interesting and reflecting Islam's rahmatan lil 'alamin. Secondly, Islamic missionary media participated in the formation of public opinion. Third, the education of Muslims based on morality. Muslims must be faithful to the teachings of religion and consistent with the religious ideal. Fourth, to maximize the source of Islamic capitalism such as zakat, as a tool to achieve the welfare of all people.* * *Globalisasi telah memengaruhi semua subsistem budaya masyarakat saat ini, terlebih di bidang media. Bagaimana peluang dakwah Islam di tengah globalisasi media merupakan fokus dari artikel ini. Studi kepustakaan telah digunakan dalam penelitian ini. Hasilnya menunjukkan bahwa posisi dakwah Islam berada di posisi terpinggirkan dan belum mampu menjadi pemain utama. Terdapat empat peluang yang bisa digunakan dalam berdakwah Islam di era globalisasi media. Pertama, kebebasan media informasi diisi dengan meningkatkan kreativitas dalam membuat konten-konten Islami yang lebih menarik dan mencerminkan Islam rahmatan lil ‘alamin. Kedua, media dakwah Islam Ikut serta menjadi pemain dalam pembentukan opini publik. Ketiga, pendidikan umat Islam berbasis moralitas. Muslim harus setia pada ajaran agama dan konsisten terhadap idealitas agama. Keempat, mendayagunakan secara maksimal sumber kapitalisme Islam seperti zakat, sebagai alat untuk mencapai kesejahteraan seluruh umat.